EBEN KIDS MINISTRY PELAYANAN ANAK VIA MEDIA DIGITAL - Mondolu, Debby Christ; Pattinama, Yenny Anita; Sitindaon, Riky Handoko; Mau, Margaritha; Siringoringo, Maruhal (PkM: Pistotites, 2021)
Abstract Using the internet as a means of nurturing and educating children is a good step during the current Covid-19 pandemic. Therefore, the community service team carried out service at the Ebenhaezer Theological College (STTE) Tanjung Enim. In this Eben Kids Ministry activity, STTE staff collaborated with the Sumbagsel Regional Council and also students in the school complex. activities outside the home. For this reason, effective action is needed to adjust to the situation, so that every program that has been launched can be implemented during the Covid-19 pandemic. Through Eben Kids Ministry shows, staff and students learn to be more creative and innovative in presenting shows so that each show can attract children's attention. Eben Kids Ministry is also designed in such a way that every child who watches the show is not only educated in spiritual matters but also develops creativity and ability in various things. Abstrak Menggunakan media internet sebagai sarana membina dan mendidik anak-anak adalah suatu Langkah yang baik di masa pandemic Covid-19 saat ini. Karena itu, tim pengabdian masyarakat melakukan kegiatan pengabdian di Sekolah tinggi Teologi Ebenhaezer (STTE) Tanjung Enim. Di dalam kegiatan Eben Kids Ministry ini, para staff STTE bekerja sama dengan Lembaga Majelis Daerah Sumbagsel dan juga Mahasiswa-mahasiswi yang ada di kompleks sekolah tersebut, Para staff dan pembina serta mahasiswa diberikan pemahaman yang baik dalam menyikapi keadaan yang saat ini membuat sulitnya ber-aktifitas diluar rumah. Untuk itu, diperlukan tindakan yang efektif untuk beradaptasi dengan keadaan, agar setiap program-program yang telah di canangkan dapat di laksanakan di masa pandemic Covid-19. Melalui tayangan Eben Kids Ministry, para staff dan mahasiswa dituntut untuk lebih kreatif dan inovatif dalam menyajikan tayangan agar setiap tayangan dapat menarik perhatian anak-anak. Eben Kids Ministry juga di design sedemikian rupa agar setiap anak-anak yang menonton tayangan tersebut tidak hanya di didik dalam hal kerohanian melainkan juga dilatih membangun kreativitas dan kemampuan dalam berbagai hal.